Reclassification of the Angraecum-alliance (Orchidaceae, Vandoideae) based on molecular and morphological data - Szlachetko, Dariusz L.; Tukałło, Piotr; Mytnik-Ejsmont, Joanna; Grochocka, Elżbieta (Biodiversity: Research and Conservation, 2013)
Results of molecular analysis compared with morphological studies were used for reclassification of the Angraecumalliance (Orchidaceae). For the purpose of this study we sequenced the ITS region (ITS1-5.8S-ITS2) of nrDNA representing nuclear genome and the plastid region trnL-F (including intron of trnL gene and trnL-trnF intergenic spacer). The ITS matrix includes 97 samples representing 86 species and the trnL-F matrix includes 94 samples representing 86 species. We focus mainly on the genus Angraecum, however the other genera of Angraecinae are also included (Aeranthes, Campylocentrum, Dendrophylax, Cryptopus, Calyptrochilum, Lemurorchis, Jumellea, Neobathiea, Oeonia, Oeoniella, Sobennikoffia). Additional 43 sequences, including an outgroup (Polystachya modesta) and other representatives of the subtribes Aeridinae (Aerides) and Aerangidinae (Aerangis, Angraecopsis, Erasanthe, Solenangis), were obtained from NCBI resources. Bayesian analysis using MrBayes 3.1.2 on the combined ITS/trnL-F matrix were performed. The monophyly of Angraecinae with an inclusion of Aerangidinae is highly supported by both methods (93 BP/100 PP). The Angraecoid taxa formed two well supported clades, namely clade I (89 BP/100 PP) and clade II (84 BP/100 PP). New classification based on both molecular and classical taxonomy studies is presented including a key to the genera. The subtribe Angraecinae includes 36 genera, 18 of them, included within Angraecum by different authors so far, are treated here. Five new genera are described: Eichlerangraecum, Hermansia, Lesliegraecum, Pectianriella and Rudolfangraecum. Ten sections of Angraecum are raised to the generic status.